Kebijakan Deviden dan Ukuran Perusahaan terhadap Nilai Perusahaan - Salsa, Zahra; Deby, Deby; Yuniarti, Rina (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2025)
This study looks at the impact of dividend policy and company size on firm value in 14 manufacturing businesses listed on the Indonesia Stock Exchange between 2021 and 2023. Using a quantitative approach and multiple regression analysis with SPSS version 26, the results show that dividend policy has a negative but small effect on firm value, whereas company size has a negative and significant impact on firm value.